HUBUNGAN KECERDASAN EMOSI DAN MINAT BELAJAR DENGAN HASIL BELAJAR MATA PELAJARAN SANITASI HYGIENE DAN KESELAMATAN KERJA KELAS X JASA BOGA SMK NEGERI 2 BUKITTINGGI - Juniyati, Fatimah; Yulastri, Asmar; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research is to find out the relation Emotional Intelligence and Study Motivation with the Study Result of SMK N 2 Bukittinggi student in academic year 2016/2017. This research is a quantitative research with correlation approach. The population of this research is 80 culinary students of Grade X and the sample is 62 students. The technique of data collective is using questionnaire with Likert scale measurement. The analysis of data is using descriptive analysis and correlational. Based on the result of the research known that the highest percentage of emotional intelligence 65%, study motivation 52%, result study 74%, with the correlation coefficient0,688. The hypothesis (Ha) accepted as there is a positive and significant correlation between emotional intelligence and study motivation with study result at sanitation hygiene and work safety lesson in SMK N 2 Bukittinggi.Keyword : Emotional Intelligence , Study Motivation, Study Result.